Digital Governance on Broadcasting Industry - Dian Wardiana Sjuchro; Akhmad Yani Surachman; Willya Achmad (Journal of Governance, 2022)
The development of media based on the internet has not dampened the existence of television broadcasts, because the penetration of information through television is still the highest. In terms of broadcast infrastructure quality, Indonesia lags behind other countries. Indonesia still uses analog channels while other countries have turned off analog broadcasts and switched to digital broadcasts. On top of that, it is necessary to describe the migration policy of analog television broadcasts to digital broadcasts that supports the improvement of television broadcast quality in Indonesia, and the prospects for the post-migration broadcast industry from analog television to digital broadcasting. The result is an analog switch off (ASO) which encourages efficient use of frequency bands in Indonesia. However, it is suspected that the implementation of digital television free-to-air (FTA) migration could damage the broadcast business structure. By 2022, there will be 103 licensed digital broadcasters and 728 broadcasters who will migrate to digital. The number of broadcasts will have an impact on the level of competition between broadcasting institutions to get cake as a source of life. In terms of nice breadth, niche overlap, and nice, all major broadcasts will still dominate the competition map in the broadcast industry. Meanwhile, local broadcasting institutions that are established in the regions will find it difficult to compete.